Mortgaging the ancestors : ideologies of attachment in Africa - Shipton, Parker MacDonald (Yale agrarian studies., 2009)
This title looks briefly at European and North American theories on private property and the mortgage, then shows how these theories have played out as attempted economic reforms in Africa.